Clinical significance of soluble CD163 in polymyositis-related or dermatomyositis-related interstitial lung disease. Issue 1 (December 2017) - Enomoto, Yasunori; Suzuki, Yuzo; Hozumi, Hironao; Mori, Kazutaka; Kono, Masato; Karayama, Masato; Furuhashi, Kazuki; Fujisawa, Tomoyuki; Enomoto, Noriyuki; Nakamura, Yutaro; Inui, Naoki; Suzuki, Daisuke; et al.
Abstract Background Macrophage activation is involved in the pathogenesis of polymyositis (PM)/dermatomyositis (DM). CD163, a scavenger receptor expressed on the surface of activated macrophages, mediates anti-inflammatory functions. This study aimed to evaluate the clinical significance of soluble CD163 (sCD163) in PM/DM-related interstitial lung disease (ILD). Methods The main subjects were 48 patients with PM/DM-related ILD. As controls, 10 patients with PM/DM without ILD and 20 healthy volunteers were enrolled. In patients with PM/DM-related ILD, the baseline characteristics and clinical course were obtained through a review of patient medical records. Serum sCD163 levels at ILD diagnosis were quantified by enzyme-linked immunosorbent assay, which were compared with the other baseline clinical factors and evaluated for potential as a prognostic biomarker. In addition, immunohistochemistry analysis using anti-human CD163 antibody was performed on the lung sections of two patients with DM-related ILD (a survivor and non-survivor, respectively) and one patient with early-stage lung cancer as a normal control. Results The median value of serum sCD163 in patients with PM/DM-related ILD was 818 ng/mL, which was higher than that of PM/DM patients without ILD and healthy volunteers (716 ng/mL and 340 ng/mL, respectively). Significant but mild correlations with serum sCD163 levels were observed for serum C-reactive protein levels (r = 0.322) and % predicted forced vital capacity (r = −0.301) in patients with PM/DM-related ILD. A Cox proportional hazard model demonstrated that patients with PM/DM-related ILD and higher sCD163 levels had worse prognosis (age-adjusted and gender-adjusted hazard ratio per 100 ng/mL increase 1.27, 95% confidence interval 1.11–1.45, P <0.001). In immunohistochemistry analysis, compared with normal lung, alveolar infiltration of CD163-positive macrophages was evident in the lungs of patients with DM-related ILD. Especially, the finding was more severe in the non-survivor's lung. Conclusions Serum sCD163 might be a potential biomarker for predicting the severity and prognosis of PM/DM-related ILD. Our results suggest the importance of macrophage activation in the disease.